Art at the limits of the visible - Zabel, Igor (Primerjalna književnost, 2004)
The article deals with the function of the non-visual, especially verbal elements, in the visual arts since the 1960s. It mentions the controversy between the modernist demand that art should be purely visual, and its conceptualist critics. It illustrates the possible use of texts in visual arts with the work of three artists, Jenny Holzer, Lewis Baltz and Joze Barši.
Keywords: Holzer, Jenny, 1950-; Baltz, Lewis, 1945-; Barši, Jože, 1955-; vizualna kultura; vizualna umetnost; tekstualnost